A review on molecular docking analysis of phytocompounds against SARS-CoV-2 druggable targets. Issue 1 (1st January 2021) - Jamiu, Abdullahi Temitope; Pohl, Carolina H.; Bello, Sharafa; Adedoja, Toluwase; Sabiu, Saheed
Abstract : The novel β-coronavirus, SARS-CoV-2, responsible for the coronavirus disease 2019 (COVID-19) emerged in China in December 2019. Due to its high transmission and infection rate, it has spread around the world and has transformed into a ravaging global pandemic with enormously unprecedented impacts globally on human, social, and economic health. Just like SARS-CoV and MERS-CoV, there is no specific antiviral drug for its treatment. The only available therapeutics are supportive and symptom-based. Thus, scientists are harnessing various strategies to expedite drug development. One such approach is drug repurposing through computational screening of phytocompounds, which leverages proteins that are essential for the entry, replication, pathogenesis, assembly, and release of SARS-CoV-2. Here, we review the available literature on molecular docking of phytoligands against SARS-CoV-2 integral proteins, in a bid to update our current knowledge and identify the most promising molecules. The overwhelming majority of the promising lead compounds are either phenolics or terpenoids. Furthermore, of the elucidated SARS-CoV-2 targets, the main protease (3CL pro ) appears as one of the most attractive druggable targets. Notably, compounds such as rutin, quercetin, luteolin, neoandrographolide, curcumin, and others with evident anti-inflammatory benefits, in addition to their predicted anti-SARS-CoV-2 properties, deserve further studies to validate their activity.